Yet another introduction to dark matter: the particle physics approach - Bauer, Martin; Plehn, Tilman (Lecture notes in physics, 2019)
History of the Universe -- Relics -- Thermal Relic Density -- - WIMP Models -- Indirect Searches -- Direct Searches -- Collider Searches -- Further Reading -- Index
Keywords: Elementarteilchenphysik; Dunkle Materie